Evaluation of the Effectiveness of Interactive Student Worksheets (LKS) in Improving Mathematics Learning Outcomes in Elementary School Students - Mubarakah, Hanifah; Abdullah, Mu’in (FONDATIA, 2025)
The limited number of studies on the use of interactive student worksheets (Lembar Kerja Siswa, LKS) in Madrasah Ibtidaiyah (Islamic elementary schools) forms the background of this research, despite the widely held belief that interactive learning materials hold significant potential for improving students’ mathematical understanding. This study aims to analyze the influence of interactive LKS utilization on the mathematics learning outcomes of fourth-grade students at MI Muhammadiyah Jimbung, Klaten Regency. A quantitative approach with a correlational design was employed, using total population sampling (N = 45). Data were collected through a 24-item Likert scale questionnaire measuring the intensity of LKS use, documentation of daily test scores as indicators of learning outcomes, and contextual classroom observations. Data analysis included descriptive statistics, assumption tests (normality and linearity), and simple linear regression using SPSS. The results show a positive and significant influence of interactive LKS use on mathematics learning outcomes (R = 0.450; R² = 0.202; B ≈ 0.383; F(1,43) = 10.889; p = 0.002). This indicates that 20.2% of the variation in mathematics learning outcomes can be explained by the intensity of interactive LKS utilization. These findings reinforce the role of interactive LKS as a key component in foundational mathematics instruction, particularly within the context of the Kurikulum Merdeka, and support the application of multimodal learning and scaffolding principles in the classroom. The study’s implications highlight the need to improve LKS design quality, provide teacher training in the development of interactive teaching materials, and encourage further experimental research using standardized test instruments to strengthen causal validity and generalizability.